2015
DOI: 10.1039/c4nr04563g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigations in stimuli responsive dendrimer-based assemblies

Abstract: Stimuli-responsive macromolecular assemblies are of great interest in drug delivery applications, as it holds the promise to keep the drug molecules sequestered under one set of conditions and release them under another. The former set of conditions could represent circulation, while the latter could represent a disease location. Over the past two decades, sizeable contributions to this field have come from dendrimers, which along with their monodispersity, provide great scope for structural modifications at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 115 publications
1
51
0
Order By: Relevance
“…Special expectations are associated with the use of these polymers as carriers of biologically and medically important molecules [1][2][3][4][5][11][12][13][14][15][16][17][18], above all of oncologic drugs [11][12][13][14][15][16][17]. In addition, it has been recently shown that these globular branched polymers have a great potential as anti-amiloydogenic agents [19,20], and as interferents in the formation of prion materials [21].…”
Section: Introductionmentioning
confidence: 99%
“…Special expectations are associated with the use of these polymers as carriers of biologically and medically important molecules [1][2][3][4][5][11][12][13][14][15][16][17][18], above all of oncologic drugs [11][12][13][14][15][16][17]. In addition, it has been recently shown that these globular branched polymers have a great potential as anti-amiloydogenic agents [19,20], and as interferents in the formation of prion materials [21].…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli‐responsive particles that exhibit changes in dimension, structure, or aggregation state in response to an internal or external stimulus have become a rapidly developing category of stimuli‐responsive materials due to their diverse range of applications, particularly in drug delivery 91–102. Multi‐stimuli‐responsive particles that respond to a combination of three or more signals represent particularly promising candidates, as demonstrated by scientists and engineers in various fields of physics, chemistry, biology, and medicine.…”
Section: Multi‐stimuli‐responsive Particlesmentioning
confidence: 99%
“…Stimuli‐responsive polymers, especially pH‐responsive nanoparticles, are intelligent system that can be widely applied in different areas . Most stimuli‐responsive polymers are based on the self‐assembly of polymeric molecules for various nanostructures such as liposomes, dendrimers, and micelles . The observed response shown in macroscale is a consequence of the conformational change of polymer molecules within the polymer system.…”
Section: Introductionmentioning
confidence: 99%